2018
DOI: 10.1038/s41379-018-0050-6
|View full text |Cite
|
Sign up to set email alerts
|

Duplications of KIAA1549 and BRAF screening by Droplet Digital PCR from formalin-fixed paraffin-embedded DNA is an accurate alternative for KIAA1549-BRAF fusion detection in pilocytic astrocytomas

Abstract: Pilocytic astrocytomas represent the most common glioma subtype in young patients and account for 5.4% of all gliomas. They are characterized by alterations in the RAS-MAP kinase pathway, the most frequent being a tandem duplication on chromosome 7q34 involving the BRAF gene, resulting in oncogenic BRAF fusion proteins. BRAF fusion involving the KIAA1549 gene is a hallmark of pilocytic astrocytoma, but it has also been recorded in rare cases of gangliogliomas, 1p/19q co-deleted oligodendroglial tumors, and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 18 publications
2
26
0
1
Order By: Relevance
“…2, g). FISH analysis confirmed 1p/19q codeletion, and droplet digital PCR analysis confirmed the KIAA1549:BRAF fusion as previously described [13]. The patient did not undergo any adjuvant treatment and after 10 years follow-up, she is still alive with no evidence of relapse nor leptomeningeal spread.…”
Section: Casesupporting
confidence: 77%
“…2, g). FISH analysis confirmed 1p/19q codeletion, and droplet digital PCR analysis confirmed the KIAA1549:BRAF fusion as previously described [13]. The patient did not undergo any adjuvant treatment and after 10 years follow-up, she is still alive with no evidence of relapse nor leptomeningeal spread.…”
Section: Casesupporting
confidence: 77%
“…In the present study, we revealed that the rate of TERT promoter mutations was 22.4% (13/ 58); additionally, this mutation was found mainly in H3wildtype tumors (9/13), and was associated with a poor prognosis for grade II/III spinal cord gliomas. The BRAF V600E mutation, KIAA1549-BRAF fusion, FGFR alterations, and MYB or MYBL1 rearrangements are key prognostic and therapeutic markers for diffuse brain gliomas with wildtype IDH and H3 in children or adolescents [3,14,15,30]. Here, we also found that BRAF V600E only occurred in H3-wildtype grade II/III spinal cord astrocytomas, and was associated with a good prognosis.…”
Section: Discussionsupporting
confidence: 58%
“…As each individual droplet is devoid of competition, each DNA fragment is amplified, allowing for unparalleled sensitivity. ddPCR can identify not only point mutations such as BRAF p.V600E [123], H3.3 p.K27M [187], IDH1 p.R132H [187], and FGFR1 p.N546K and p.K656E [58] but also CDKN2A deletions [123], KIAA1549-BRAF [5], and FGFR1 TKD-duplication [58] based on copy number comparisons. This technique is very robust on degraded DNA, including from FFPE material, and requires minimal technical hands-on time.…”
Section: Droplet Digital Pcrmentioning
confidence: 99%